Spasmolytic and Uroprotective Effects of Apigenin by Downregulation of TGF-β and iNOS Pathways and Upregulation of Antioxidant Mechanisms: In Vitro and In Silico Analysis - Saima; Irfan Anjum; Aisha Mobashar; Shah Jahan; Saima Najm; Hiba-Allah Nafidi; Yousef A. Bin Jardan; Mohammed Bourhia (MDPI AG, 2023)
Apigenin is a phytochemical obtained from Chamomilla recutita. Its role in interstitial cystitis is not yet known. The present study is aimed at understanding the uroprotective and spasmolytic effects of apigenin in cyclophosphamide-induced interstitial cystitis. The uroprotective role of apigenin was analyzed by qRT-PCR, macroscopic analysis, Evans blue dye leakage, histological evaluation, and molecular docking. The spasmolytic response was measured by adding cumulative concentrations of apigenin to isolated bladder tissue pre-contracted with KCl (80 mM) and carbachol (10−9-10−4) on non-incubated and pre-incubated tissues with atropine, 4DAMP, methoctramine, glibenclamide, barium chloride, nifedipine, indomethacin, and propranolol. Apigenin inhibited pro-inflammatory cytokines (IL-6, TNF-α and TGF 1-β) and oxidant enzymes (iNOS) while increasing antioxidant enzymes (SOD, CAT, and GSH) in CYP-treated groups compared to the control. Apigenin restored normal tissue of the bladder by decreasing pain, edema, and hemorrhage. Molecular docking further confirmed the antioxidant and anti-inflammatory properties of apigenin. Apigenin produced relaxation against carbachol-mediated contractions, probably via blockade of M3 receptors, KATP channels, L-type calcium channels, and prostaglandin inhibition. While the blockade of M2 receptors, KIR channels, and β-adrenergic receptors did not contribute to an apigenin-induced spasmolytic effect, apigenin presented as a possible spasmolytic and uroprotective agent with anti-inflammatory, antioxidant effects by attenuating TGF-β/iNOS-related tissue damage and bladder muscle overactivity. Thus, it is a potential agent likely to be used in treatment of interstitial cystitis.